2006
DOI: 10.4321/s0004-06142006000600007
|View full text |Cite
|
Sign up to set email alerts
|

Nuevo sling masculino "ARGUS" para el tratamiento de la incontinencia urinaria de esfuerzo

Abstract: 1. It is a safe, easy to implant, reproducible system, with few complications and a good cost-benefit relation. 2. Results are comparable to the gold standard, but it has the following advantages: immediate voiding control recovery and no need for patient training. 3. This article does not intend to show our short experience with only five cases, but we want to mention that all of them are continent with a good quality of life. 4. Our objective will be to publish our results when we can show a minimal follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Surgical techniques were applied as proposed by original authors and are described, in summary, below ( 4 - 6 ). All procedures were performed by the same surgeon: patients were submitted to regional anesthesia, in the lithotomy position and legs flexed at close to 90 degrees at the thigh level.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical techniques were applied as proposed by original authors and are described, in summary, below ( 4 - 6 ). All procedures were performed by the same surgeon: patients were submitted to regional anesthesia, in the lithotomy position and legs flexed at close to 90 degrees at the thigh level.…”
Section: Methodsmentioning
confidence: 99%
“…Two SUSs were available in the Brazilian market at the time of recruiting for this research: Argus T ® -(Promedon–Cordoba, Argentina) ( 4 , 5 ) and Advance ® (American Medical Systems-Minnetonka, United States) ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure was first described by Sierra et al . [41] In a cohort of 48 patients with a mean follow-up of 7.5 months Romano et al , showed a cure rate of 73%. As concerns major complications, the sling was removed in five cases due to urethral erosion and infection in three (6%) and two (4%) patients, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[39] A new transobturator male sling system (AdVance, American Medical Systems) has been approved by the Food and Drug Administration in the United States. The results were presented by Dr. Rehder at the American Urology Association meeting in Atlanta, GA, 2006.…”
Section: New Developmentsmentioning
confidence: 99%